Carbon Content of Electricity Futures in Phase II of the EU ETS - Harrison Fell; Beat Hintermann; Herman R. J. Vollebergh (Center for Economic Studies and ifo Institute (CESifo), 2013)
We estimate the relationship between electricity, fuel and carbon prices in Germany, France, the Netherlands, the Nord Pool market and Spain, using one-year futures for base and peak load prices for the years 2009-2012, corresponding to physical settlement during the second market phase of the EU ETS. We employ a series of estimation methods that allow for an increasing interaction between electricity and input prices on the one hand, and between electricity markets on the other. The results vary by country due to different generation portfolios. Overall, we find that (a) carbon costs are passed through fully in most countries, and perhaps even by more than 100%; (b) under some model specifications, cost pass-through is similar during peak and during base load for France, Germany and the Netherlands; and (c) the results are sensitive to the degree of cross-commodity and cross-market interaction allowed. We further find that coal prices are negatively and gas prices are positively associated with allowance prices, although the latter effect is not statistically significant in all specifications.
Keywords: Q48; Q52; Q53; Q58; 330; cost pass-through; electricity markets; EU ETS; cointegration; carbon content; renewables